EFFECTS OF TASK-BASED LANGUAGE TEACHING ON THAI KINDERGARTEN 3 STUDENTS’ CHINESE SPEAKING SKILLS AND CONFIDENCE: A CASE STUDY OF A TRILINGUAL SCHOOL IN BANGKOK - Wang, Hao; Tananuraksakul, Noparat (Journal of Buddhist Education and Research (JBER), 2023)
Task-based language teaching (TBLT) is central to goal-oriented activities in three sequential stages students use their learned target language knowledge to accomplish a real outcome. This experimental study implemented TBLT to enhance Thai kindergarten 3 (K3) students’ ability to use 80 Chinese vocabulary they circularly learned in their kindergartens 1 and 2 to express themselves verbally and meaningfully (Chinese speaking skills) and their confidence in speaking the language characterized by their learning behaviors. A sample group of 14 students at a trilingual education school in Bangkok was conveniently selected for the one group pre-test-post-test design. A 16-week lesson plan as the treatment from May to September, 2022, Chinese speaking tests and weekly assessments and video records of the whole teaching and learning processes for the purpose of inter-rater reliability were instruments to test the first hypothesis; observations through the video records were used to test the second hypothesis. Data analyzed by paired-t test confirmed the first hypothesis in that TBLT could affect the students’ Chinese speaking skills positively with statistically significant differences at .000 (P<0.05) and that game tasks gave them more chances to speak Chinese. Data analyzed by a frequency distribution supported the second hypothesis in that TBLT could affect their confidence in speaking Chinese gradually and positively, which manifested in their active responses to the researcher and discussions with their classmates in group work, enthusiasm to observe how to do different tasks and willingness to ask the researcher for help and assist others during the lessons they liked and the tasks that suited them. These findings suggested that TBLT enabled the K3 students in the present context to use their learned Chinese vocabulary in previous years to express themselves verbally and meaningfully with confidence. Implementations of TBLT for K2 and K3 students at the target school are recommended.